Evidence for mantle exhumation since the early evolution of the slow-spreading Gakkel Ridge, Arctic Ocean. (July 2018) - Lutz, Rüdiger; Franke, Dieter; Berglar, Kai; Heyde, Ingo; Schreckenberger, Bernd; Klitzke, Peter; Geissler, Wolfram H.
Highlights: Rotated basement blocks define the crustal architecture in the Eurasia Basin from the initial opening onwards. We propose that predominantly exhumed serpentinized mantle forms the basement in the Eurasia Basin, at least at the studied sector. Detachment faults that expose rocks from deep below the slow-spreading mid-ocean ridge are proposed, maintaining a process of mantle exhumation. Abstract: We study the basement configuration in the slow-spreading Eurasia Basin, Arctic Ocean. Two multichannel seismic (MCS) profiles, which we acquired during ice-free conditions with a 3600 m long streamer, image the transition from the North Barents Sea Margin into the southern Eurasia Basin. The seismic lines resolve the up to 5000 m thick sedimentary section, as well as the crustal architecture of the southern Eurasia Basin along 120 km and 170 km, respectively. The seismic data show large faulted and rotated basement blocks. Gravity modeling indicates a thin basement with a thickness of 1–3 km and a density of 2.8*10 3  kg/m 3 between the base of the sediments and the top of the mantle, which indicates exhumed and serpentinized mantle. The Gakkel spreading ridge, located in northern prolongation of the seismic lines is characterized by an amagmatic or sparsely magmatic segment. From the structural similarity between the basement close to the ultra-slow spreading ridge and our study area, we conclude that the basement in the Eurasia Basin is predominantly formed by exhumed and serpentinized mantle, with magmatic additions. An initial strike-slip movement of the Lomonosov Ridge along the North Barents Sea Margin and subsequent near-orthogonal opening of the Nansen Basin is supposed to have brought mantle material to the surface, which was serpentinized during this process. Continuous spreading thinned the serpentinized mantle and subsequent normal faulting produced distinct basement blocks. We propose that mantle exhumation has likely been active since the opening of the Eurasia Basin.